VLT/NACO astrometry of the HR 8799 planetary system: L′-band observations of the three outer planets - Bergfors, Carolina; Brandner, W.; Janson, M.; Köhler, R.; Henning, Thomas (Astronomy and astrophysics, 2011)
Context. HR 8799 is so far the only directly imaged multiple exoplanet system. The orbital configuration would, if better known, provide valuable insight into the formation and dynamical evolution of wide-orbit planetary systems.Aims. We present data which add to the astrometric monitoring of the planets HR 8799 b, c and d. We investigate how well the two simple cases of (i) a circular orbit and (ii) a face-on orbit fit the astrometric data for HR 8799 d over a total time baseline of ~2 years.Methods. The HR 8799 planetary system was observed in L′-band with NACO at VLT.Results. The results indicate that the orbit of HR 8799 d is inclined with respect to our line of sight, and suggest that the orbit is slightly eccentric or non-coplanar with the outer planets and debris disk.